Finding the Best Analysis for the Sleeper Cells of Terrorist Acts in the Crowded Areas of Human Activities in the City of Baghdad - Al-Ramahi , Fouad K. Mashee; Mahmood, Faleh H.; Ali, Ali K. Mohammed (Iraqi Journal of Science, 2023)
Terrorist operations disturbed societies and threatened their existence due to destructive ideas carried by those groups that believe in radical change and the use of multiple methods to implement their ideas, as well as taking methods of concealment among society, so it has become difficult to detect them. The study's purpose is to locate sleeper cells of terrorist operations in areas dense with various human activities using remote sensing techniques and geographic information systems programs. The programs were used to analyze the group of terrorist incidents data that occurred in Baghdad in 2011 and study how to limit the crimes spreading in Baghdad. The study included building a model in spatial information systems for sites by identifying the accidents by simulating the reality with the Global Positioning System (GPS) to be a starting point for the spatial analysis of the accidents and devising a scientific approach to locate sleeper cells using statistical methods and theories. Moreover, predictive research focuses on several spatial studies to produce predictive maps for the sleeper cell sites spreading from their location toward the cities. The GIS proved to be one of the primary software packages that help decision-makers take appropriate measures at the right time, predict the spatial spread of future accidents, and control them in the future to be an effective model for researchers.